KONFIRMASI INTEGRATIF MORFOLOGI DAN DNA BARCODING IKAN SEBELAH YANG KEKURANGAN DATA DI PERAIRAN CILACAP, INDONESIA: INTEGRATIVE MORPHOLOGICAL AND DNA BARCODING CONFIRMATION OF THE DATA-DEFICIENT INDIAN HALIBUT IN CILACAP WATERS, INDONESIA - Sugeng Hartono; Ani Haryati; Sahda Salsabila; Fajar Adiyanto; Purnama Sukardi; Gondo Puspito; Idris Abdulrahman (Jurnal Teknologi Perikanan dan Kelautan, 2026)
The Indian halibut (Psettodes erumei) is classified as data deficient on the IUCN Red List. Accurate species identification is a fundamental prerequisite for sustainable fisheries management and biodiversity conservation. This study aims to identify the Indian halibut landed from Cilacap waters, Indonesia, using an integrative morphological and molecular approach. Four specimens collected in March and June 2025 were analyzed using an integrated morphological and molecular approach. Morphological identification was based on detailed morphometric and meristic analyses, cross-referenced with standard taxonomic guides. Molecular identification involved DNA extraction, PCR amplification of the mitochondrial Cytochrome C Oxidase Subunit I (COI) gene, electrophoresis, sequencing, and comparison with global genetic databases using BLAST. Morphological characteristics aligned with the description of P. erumei, though significant morphometric differences from a historical reference suggest potential local phenotypic variation. DNA barcoding confirmed the identity with 100% sequence similarity to conspecifics from other Indo-Pacific regions (GenBank accession: PX599017.1). Phylogenetic analysis further placed the Cilacap samples within a genetically homogeneous cluster of P. erumei from across Indonesian waters. This research successfully contributes to Indonesia's biodiversity database and DNA barcode library for a commercially exploited yet understudied species. It also provides essential baseline data to inform stock assessments and conservation strategies in the region.